2007
DOI: 10.1007/s11250-007-9013-5
|View full text |Cite
|
Sign up to set email alerts
|

Breeding goals for the Kenya Dual Purpose goat. II. Estimation of economic values for production and functional traits

Abstract: Economic values for production traits (milk yield, MY, kg; 12-month sale weight, LW, kg; consumable meat percentage, CMP) and functional traits (doe live weight, DoWT, kg; number of kids weaned, NKW; kidding frequency, KF; kidding rate, KR, %; doe weaning rate, DoWR, %; doe survival rate, DoSR, %; post-weaning survival rate, PoSR, %; pre-weaning survival rate, PrSR, % and; residual feed intake of yearlings, RFIgamma, kg and does RFId, kg) were estimated for the Kenya Dual Purpose goat (KDPG) for systems under … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Investigating the economic returns of smallholder low, medium and high potential goat farm-ing systems in Kenya, Bett et al (2007b) reported that the positive economic values for most traits under fixed flock-size and fixed feed resource scenarios indicates that a unit increase in genetic merit for the traits would have a positive effect on the profitability of the systems. This underscores the value of the two fundamentals for goat meat production, nutrition and genetic improvement individually and the interaction between the two.…”
Section: Nutritionmentioning
confidence: 99%
“…Investigating the economic returns of smallholder low, medium and high potential goat farm-ing systems in Kenya, Bett et al (2007b) reported that the positive economic values for most traits under fixed flock-size and fixed feed resource scenarios indicates that a unit increase in genetic merit for the traits would have a positive effect on the profitability of the systems. This underscores the value of the two fundamentals for goat meat production, nutrition and genetic improvement individually and the interaction between the two.…”
Section: Nutritionmentioning
confidence: 99%
“…However, this result was in contrast with Gizaw et al (2018), who found a positive economic value for the mature weight of Menz sheep. On the other hand, negative and positive economic values of doe live weight were also reported for Kenyan dual-purpose goats (Bett et al, 2007) in three different production systems. Thus, differences may be due to variability in flock size, species, individual genetic variation, management, place and year of the studies.…”
Section: Breeding Objectives Using Bioeconomic Modelmentioning
confidence: 88%
“…Economic values are needed for each trait in the breeding goal to ensure that selection emphasis is proportional to the economic importance of each of these traits (Amer et al, 2001). Economic values for traits in the breeding goal for KDPG will be estimated in the companion paper (Bett et al, 2006).…”
Section: Discussionmentioning
confidence: 99%